THE INFLUENCE OF AUDIT COMMITTEE INDEPENDENCE TO EARNINGS MANAGEMENT - Mursalmina Mursalmina (SHIBGHAH: Journal of Muslim Societies, 2019)
This research has objectives to investigate The Influence of Audit Committee independence to Earnings Management as well as to study the Islamic framework. Using library Analysis as the research method, this paper focuses on the characteristics of the audit committee independence. The analysis shows that Independence are very important to monitoring earning management. four characters that the audit committee must possess to achieve independence, namely: Siddiq, Amanah, Tabligh, and Fathanah.